Bayesian spatial modeling of adolescent pregnancy risk through integrated nested Laplace approximation in Chiapas, 2015 - Núñez Medina, Gerardo (2019)
The objective of the study is to analyze the spatial distribution of adolescent municipal fertility in Chiapas during 2015. Method: from the use of estimated structural additive models through the integrated nested approach of Laplace. Results: A first model identifies the non-random spatial patterns of fertility, while a second model analyzes the effect of cofactors such as poverty, marginalization and illiteracy on the spatial distribution of adolescent fertility. Discussion: The results seem to confirm that the spaces where higher rates of marginalization, illiteracy and poverty are registered increase the risk of setting up a cluster where the adolescent fertility rates observed are on average higher than those presented by neighboring municipalities.